IMPLEMENTASI SYSTEM LOYALTI MANAJEMEN (RENATA) MENGGUNAKAN FRAME WORK LARAVEL 9 STUDI KASUS AGUNG TOYOTA KUTA - I Made Putra Mahayasa; I Nyoman Bagus Suweta Nugraha; Ni Luh Gede Ambaradewi (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Loyalty programs are designed to encourage and maintain customer loyalty to a brand, company, or product. In these programs, customers are often given incentives, rewards, or special benefits in exchange for repeat purchases or other desired behaviors. The primary goal of loyalty programs is to increase customer retention, strengthen the relationship between the brand and customers, and enhance the customers' lifetime value. To identify loyal customers at Agung Toyota Kuta, a tool is needed to expedite the determination of customer status. In this research, data collection methods through interviews and observations are complemented by conducting literature studies on books, theses, journals, data collection, and references that support this research. The system development method uses the waterfall method, and the program design uses the Laravel framework. The implemented system is expected to help determine loyal customers so that it can provide various types of benefits, such as discounts, access to exclusive offers, or other special treatments to loyal customers. The company can enhance its promotional strategies and communication systems so that customers become more aware of the workshop's loyalty program. By providing accurate information systems regarding customer loyalty programs that are accessible to those concerned.